Plan, activity, and intent recognition : theory and pratice - Sukthankar, Gita. (Waltham, MA : Morgan Kaufmann, 2014)
Plan recognition, activity recognition, and intent recognition together combine and unify techniques from user modeling, machine vision, intelligent user interfaces, human/computer interaction, autonomous and multi-agent systems, natural language understanding, and machine learning.
Part 1: Plan and goal recognition -- Part 2: Activity discovery and recognition -- Part 3: Modeling human cognition -- Part IV: Multiagent systems -- Part V: Applications.
Print version record.
Includes bibliographical references and index.
Keywords: Human activity recognition; Artificial intelligence; Pattern perception; Intention; COMPUTERS -- General; Artificial intelligence; Human activity recognition; Intention; Pattern perception; Signal Processing, Computer-Assisted.; Intention; Electronic books; Electronic books